Pengaruh Viral Marketing, Brand Image, dan e-WOM terhadap Minat Beli Produk Somethinc pada Followers Instagram @somethincofficial - Ananda Nabilaturrahmah; Salim Siregar (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research was conducted to analyze to provide knowledge and explanations about consumer buying interest in SomeThinc products through viral marketing, brand image, and e-wom. Quantitative methods with verification and descriptive approaches are the methods used in this research. Data were collected using questionnaires and library studies with the object of research being Instagram followers @somethincofiicial with a total of 400 respondents. Path analysis using a range of scales is an analytical tool contained in this study. The results showed that viral marketing on buying interest was in very good criteria, while brand image and e-wom on buying interest were in good criteria. In the results of the t-test, it can be explained that the significant value of viral marketing is (0.000) < (0.05), brand image (0.000) < (0.05), and e-wom (0.013) < (0.05) which can mean that viral marketing, brand image, and e-wom have a positive and significant influence on buying interest. Then there is a simultaneous influence between viral marketing, brand image, and e-wom on buying interest by 69.4% and the remaining 30.6% from other factors not examined in this study.